2011
DOI: 10.1111/j.1742-1241.2011.02793.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment and the prospect of pharmacogenetics in Parkinson’s disease

Abstract: Summary Parkinson disease (PD) is a progressive movement disorder marked by tremor, rigidity, bradykinesia and postural instability. Levodopa (l‐dopa), usually combined with a peripheral dopa decarboxylase inhibitor, has been proved to provide the best symptomatic benefit for PD. However, its long‐term efficacy is limited because of motor complications and drug‐induced dyskinesia. Dopamine agonists, catechol‐O‐methyltransferase inhibitors and monoamine oxidase‐B inhibitors are anti‐parkinsonian (anti‐PD) drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 55 publications
(76 reference statements)
0
28
0
Order By: Relevance
“…Studies in levodopa-naïve MPTP animal models have demonstrated that higher dose and frequency of levodopa administration led to more severe and intense dyskinesia [6,7]. In addition, pharmacogenetic factors, such as polymorphisms of the catechol-o-methyl transferase gene and dopamine receptor gene, particularly the DRD2 receptor may also increase the genetic susceptibility for developing dyskinesia [8].…”
Section: Introductionmentioning
confidence: 98%
“…Studies in levodopa-naïve MPTP animal models have demonstrated that higher dose and frequency of levodopa administration led to more severe and intense dyskinesia [6,7]. In addition, pharmacogenetic factors, such as polymorphisms of the catechol-o-methyl transferase gene and dopamine receptor gene, particularly the DRD2 receptor may also increase the genetic susceptibility for developing dyskinesia [8].…”
Section: Introductionmentioning
confidence: 98%
“…Perhaps the most urgent need is for the development of therapeutic approaches to arrest, stabilize, or reverse the progression of neurodegeneration. The current use of L-dopamine (L-dopa), a precursor of dopamine, for Parkinson’s disease, to improve motor function and patient quality of life, has a limited long-term efficacy due to motor complications and drug-induced dyskinesia [13]. Likewise riluzole, the only drug approved for ALS, and the antipsychotics and neuroleptics used in Huntington’s disease only have modest beneficial effects to extend patient survival [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Almost a century ago, Cohn described seborrhoea as a symptom of postencephalitic Parkinson's disease . Much later, these findings were replicated in patients with both postencephalitic and idiopathic Parkinson's disease, characterised by a loss of dopaminergic neurons in the substania nigra . Interestingly, although sebum production was increased in patients with various neurological diseases, the association with seborrhoea was only statistically significant in patients with Parkinson's disease: both postencephalitic and idiopathic .…”
Section: Historical Perspectivementioning
confidence: 99%